Analysis of the Implementation of Business Strategies in Increasing the Competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Cendana District, Enrekang Regency - Hanisa, Nur; Rizal S, Muh; Kasmita, Maya; Rivai, Andi Muhammad (Pinisi Business Administration Review, 2025)
Analysis of the Application of Business Strategies in Increasing the Competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Cendana District, Enrekang Regency, Thesis, Faculty of Social Sciences and Law, Department of Administrative Sciences, Business Administration Study Program, Makassar State University. Guided by Muh Rizal and Maya Kasmita. This study aims to determine the implementation of business strategies and factors that affect the competitiveness of Micro Business actors. The method used in this research is qualitative method, which is a research method used to examine natural objects, where researchers are key instruments. Data collection techniques through observation, interviews, and documentation, informants from this study amounted to six people consisting of six micro entrepreneurs in Cendana District, Enrekang Regency. The results show that every Micro business actor seeks to improve the position of their products in competition in the market, because products are outputs of production process activities offered to the market to get attention, bought, used or consumed that can satisfy wants or needs and are one of the factors that can affect competitive advantage. Supporting factors that affect competitiveness are products offered that are durable / durable, business actors always innovate on their respective products, have their own unique products, the prices offered are very stable while the inhibiting factors are the use of social media that is not optimal, the ability to collect information on consumer needs is still lacking, and sales distribution is still limited in Enrekang Regency. Keywords : Business strategy, MSMEs, competitiveness